(untitled) (Tarbiyah Suska Conference Series, 2022)
Writing is an activity to express ideas, ideas, and opinions through writing. For elementary school students, they are able to think logically on their own knowledge, but have difficulty in writing ideas because they cannot think abstractly so that real images are needed to build and connect information. One method that helps students’ writing skills and activeness is the field trip method, in which students review, observe, and learn an object by visiting a place. The purpose of this research is to see how much influence the Field Trip Method has on the learning outcomes of third grade students in Rumbai District, Pekanbaru. Quasy Experiment Control Group is used as a type of research. The sampling technique consists of two stages, namely multi-stage sampling and purposive sampling. The results of this research show: (1) the effect of the field trip method on the learning outcomes of experimental class students, with an average value of 90.05 which is greater than the control class with an average of 68.55 with the results of t_count = 4.046 and t table = 2.048, and (2) the effect of the field trip method on student learning outcomes from t_count = 3.621 and t_table 2.086 with a significance value of 0.002 <0.05.